Effect of Life Review Therapy on self-actualization and Happiness of the Elderly in Iran - Naseh Mohammadi Safa; Seyed Jalal Younesi; Mahshid Foroughan; Sina Ahmadi; Mohammad Rostami (Sālmand, 2024)
Objectives Older people experience physical and psychological changes that can negatively affect their life satisfaction and result in unhappiness. Life review therapy can be an effective intervention in increasing the positive feelings and happiness of the elderly. This study aims to determine the effects of a life review therapy program on self-actualization and happiness among older adults. Methods & Materials This is a quasi-experimental study with a pre-test/post-test/follow-up design. Participants were 22 elderly people aged ≥60 years referred to a daycare center in Tehran, Iran. They were randomly divided into two intervention (n=11) and control (n=11) groups. The perma flourishing scale and the Oxford happiness questionnaire were used to collect data before, immediately after, and one month after the intervention. The life review therapy was performed according to Haight and Webester’s protocol. The collected data were analyzed in SPSS software, version 26. Results There was a significant increase in the total mean scores of happiness and flourishing scores in the intervention group immediately and one month after the intervention (P<0.001), but no significant change was reported in the control group. The mean scores of happiness and flourishing in the intervention group in the pre-test phase were 50.27 and 98.63, respectively. In the post-test and follow-up phases, these scores reached 58.27 and 57.09 for happiness and 111.63 and 104.81 for flourishing, respectively. Conclusion The present study shows that life review intervention in can provide an opportunity for flourishing and psychological development and also an increase in the level of happiness among older adults.